MÉTODO DEL PUNTO PROXIMAL y SUS APLICACIÓN A MODELOS ECONÓMICOS - De La Cruz Cuadros, Lucy Haydee (2012)
The aim of this work is to study the convergence of a extension of the proximal point method for minimizing a class of nonconvex functions on the nonnegative orthant and give some applications of the method in the solution of economics models which appears in microeconomy. The used procedures were the collection of information in scientific journals and specialized books, the study of the same and finally the use of mathematical tools to study the convergence of the sequence of the method. The results show that, under some appropriate assumptions, the iterations generated by the method are well defined and the sequence converges weakly to a KKT point.